A rare case of Doege-Potter syndrome: Anesthesia considerations for the surgical removal of a benign solitary lung fibrous tumor - J Indragandhi; R Krishnaprabu (Saudi Journal of Anaesthesia, 2025)
Non-Islet Cell Tumor Hypoglycemia (NICTH) associated with solitary fibrous tumor is referred to as Doege-potter syndrome (DPS). Non-Islet Cell Tumor Hypoglycemia (NICTH) is a paraneoplastic syndrome characterized by hypoglycemia from secretion of insulin-like growth factor type 2 (IGF-2). Surgical resection of massive Solitary Fibrous Tumor of Pleura (SFTP) can be complicated by airway collapse, vascular compression, hemodynamic instability and hemorrhage. SFTP patients present with metabolic derangements secondary to paraneoplastic processes. We present a case of successful removal of massive right-sided SFTP via posterolateral thoracotomy and discuss the perioperative considerations for which providers should be familiar.